The coexistence center for elderly people and its importance in the support to the family and the Health Care Network - Flávia Maria Derhun; Giovana Aparecida de Souza Scolari; Vivian Carla de Castro; Maria Aparecida Salci; Vanessa Denardi Antoniassi Baldissera; Lígia Carreira (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: To know the perception of relatives of elderly people about the coexistence center and its importance in supporting the Health Care Network. Methodology: A qualitative study carried out with 14 relatives of elderly people participating in a coexistence center. Data collection took place in January 2016 through individual interviews, which were recorded, transcribed and submitted to content analysis. The results were discussed in the light of the theoretical referential of health promotion. Results: The elderly's participation in the coexistence center was an alternative to support care and institutionalization, provided time for self-care and to maintain or engage in the formal labor market and positively influenced the family relationships. Conclusion: The coexistence center was set up as a health promotion institution, being jointly responsible for the care of the elderly with the Health Care Network and the families.